Gratitude growing from overcoming differences : A phenomenological hermeneutic study of the lived experience of Filipino patients at Landspitali - National University Hospital in Iceland - Requierme, Gwendolyn (2006)
Verkefnið er lokað til 09.10.2030. The aim of this research is to describe richly the Filipino patients’ lived experience and thereby give meaning to their experience in order to gain a new and different understanding. This phenomenological hermeneutic study of what is it like to be a Filipino patient at Landspítali – National University Hospital in Iceland? is guided by van Manen’s steps to describe and understand the lived experience with a Gadamerian perspective. Eight Filipino participants, purposefully selected, (three males and five females), aged 30-75 years, who have resided in Iceland for 3-16 years and been hospitalised on various wards of LSH, were interviewed. The interview was conducted in Philippines languages, i.e. Tagalog and Cebuano, and no interpreter was used. Three main themes emerged: the first theme is Filipino patients’ hidden emotions in their initial stage of hospitalisation. At this stage, they felt various types of fear: fear of being alone, and of lack of knowledge. Only a few of them felt indignation, for instance over being discriminated against, and the feeling of being not prioritised because of being a Filipino. The second theme recognises the conflicts arising from the differences between FPs’ rooted traditions and beliefs and the hospital’s culture. The first difference referred to physiological concerns, with emphasis on the patients’ mobility, and grooming and bathing. The second refers to psycho-social concerns, where psychological needs on family, privacy and spiritual issues, and differences in services were identified. The last theme describes how Filipino patients’ overcoming differences helped them to adjust to another culture by learning Icelandic ways and becoming confident. Moreover, finding other support, for instance from spiritual faith and from staff, fellow-patients and other Filipinos, promoted a sense of belongingness, and their gratitude at being “admitted” emerged. Therefore it is important to understand and respect cultural background in order to address ...